Stability and Sterility of Extemporaneously Prepared 0.01% Atropine Ophthalmic Solution in Artificial Tears and Balanced Salt Solution - Sri-in, Jureeporn; Sisan, Waraphorn; Kingkhangphloo, Phonphailin; Jutasompakorn, Pinpilai; Chandranipapongse, Weerawadee; Chatsiricharoenkul, Somruedee; Buranakan, Onchira; Pornseth, Arpha; Surachatkumtonekul, Thammanoon (Siriraj Medical Journal, 2022)
Objective: The aim of this study was to investigate the physicochemical and microbiological stability of extemporaneously prepared 0.01% atropine ophthalmic solution in unopened eyedropper and in simulated use condition. Materials and Methods: Two formulations of 0.01% atropine solutions, atropine in artificial tear and atropine in balanced salt solution (BSS), were prepared using 0.5 mL insulin syringes. In unopened conditions, 0.01% atropine solutions were stored for six months at refrigerated temperature (2-8°C) or room temperature (25±2°C). Visual inspection, atropine quantification, pH measurements, and sterility assay were analyzed at baseline, and every month for six months. In simulated use condition, 0.01% atropine solutions stored at refrigerated and room temperature were analyzed at 0, 15 and 30 days. Results: In unopened conditions, both of 0.01% atropine formulations stored at refrigerated temperature showed satisfactory stability. Atropine remained within 90% to 110% of the initial concentration up to six months. Under room temperature, both formulations of atropine were less than 90% of their initial value after 4 months storage. In simulated use condition, atropine concentration was within 90% to 110% of initial value after 30 days at refrigerated and room temperature. All atropine solutions prepared in artificial tear and BSS were free from bacterial contamination throughout the study. No alteration of physical appearance (i.e., precipitation, discoloration) was observed, and pH values also remained nearly unchanged. Conclusion: Both formulations of 0.01% atropine are physicochemically stable for up to 6 months when kept unopened in refrigerator, and for 1 month at refrigerated and room temperatures in simulated use condition.